Photodiode based on epitaxial silicon with high sensitivity at the wavelength 254 nm - Dobrovolskyi, Yu.; Pidkamin, L.; Brus, V.; Kuzenko, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
A mathematical model of the construction of silicon photodiode based on
epitaxial structure enabling to regulate the absorption edge of silicon in the long-wave
spectral range is presented. The suggested model allows calculating the construction that
possesses low sensitivity for the wavelengths larger than 600 nm and maximal values
near the wavelength 254 nm.